Kontribusi Self Efficacy Pada Work Engagement Ibu Yang Bekerja Sebagai PNS Di Kota Padang Panjang - Handayani, Fitri; Guspa, Anindra (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2023)
The purpose of this study was to examine the contribution of self efficacy to the work engagement of mothers who work as civil servants in Padang Panjang City. Data collection uses a quantitative approach with cluster sample technique, involving 100 mothers who work as civil servants in Padang Panjang City. Data collection was carried out using the UWES-9 scale by Schaufeli aspects as a work engagement measurement tool and a self efficacy measurement tool developed from Bandura aspects. Simple regression analysis was used in analyzing the data in this study. The results of the analysis state if there is a contribution of self efficacy to the work engagement of mothers who work as civil servants in Padang Panjang City.